Optical tissue clearing and 3D imaging of intact primate testicular tissue: a novel technology development - Pauline Wanjiku Kibui; Sarah Weischer; Nicola von Ostau; Jochen Hess; Nils Kirschnick; Thomas Zobel; Stefan Schlatt (PLoS ONE, 2025)
Classical histology struggles to preserve three-dimensional spatial context, prompting the emergence of optical tissue clearing techniques that enable imaging of intact specimens at cellular or subcellular resolution. These techniques have revolutionised fields like cell biology, developmental biology, and neuroscience. However, their application in reproductive biology remains unexplored – particularly in studying the complexities of testicular development. We developed a novel, efficient and affordable toolbox for studying intact testicular tissues, PT-CLEAR3D, that stands for primate testis – whole mount staining, tissue clearing and three-dimensional imaging. Intact testicular tissues from humans (transgender model), common marmosets and macaques underwent antibody labelling, clearing with organic solvents, and three-dimensional imaging using light sheet fluorescence microscopy. Marker specificity was confirmed by immunofluorescence staining of 3 and 25 µm testicular sections, followed by imaging with confocal microscopy. The testicular structure was evaluated using several markers: spermatogonia (melanoma-associated antigen 4), least differentiated spermatogonia (Piwi-like protein 4), Sertoli cells (vimentin and SRY-Box transcription Factor 9), peritubular myoid cells and vasculature (alpha-smooth muscle actin), and NucSpot as a nuclear dye. PT-CLEAR3D efficiently achieved optical transparency while a commercial kit that was run in parallel was inefficient. This study presents a pioneering three-dimensional visualization of intact testicular samples of up to 50 mm 3 in size and imaging depth of up to 4.5 mm across three primate species. Remarkably, PT-CLEAR3D revealed critical details at both tissue and cellular levels such as the spatial distribution of germ and somatic cells, cellular bridges, and vasculature. Furthermore, PT-CLEAR3D enabled three-dimensional reconstructions that effectively reduces confirmation bias enhancing our observation of spermatogonial clones organized as single cells, pairs, and quartets. Importantly, it adeptly identified testicular pathology and the persistence of germ cell clones in select tubules within the transgender testis following hormonal suppression of spermatogenesis. This technological development offers a versatile toolbox with benefits such as applicability across multiple species, fluorophore multiplexing, compatibility with different fixatives and deep tissue volumetric imaging with cellular resolution. Overall, PT-CLEAR3D establishes a foundation for spatial evaluation of testicular development, presenting substantial potential for advancing our understanding of the intricate kinetics of spermatogenesis in health and disease.